Protein-Hydrocolloids Interactions in "Keropok Lekor" - Kaw, Zay Ya (2004)
Basic formulation of 'keropok lekor' was developed through a sensory evaluation exercise. A fish to starch ratio of 3:2 and a ratio of sago to tapioca starch of 3:l were found to be the best formulation. The optimum levels of salt L and sugar in the formulation were 2.5% and 3.8%, based on total weight of fish and starch, respectively. Effect of selected hydrocolloids i.e. xanthan, carrageenan and locust bean gums at 0,1,2, and 3% of incorporation on acceptability, structure stability and shelflife of 'keropok lekor' was also studied. Incorporation of 2% locust bean gum significantly increased the sensory acceptability and structure stability of final product. The shelf life of the 'keropok lekor' gel was also enhanced by the incorporation of 2% locust bean gum by 4 day. Addition of all the hydrocolloids increased gelatinization temperatures of sago starch by 4-6°C and decreased the enthalpy (AH) of the gelatinization by 0.5 to 2.3Jlg. The AH of gelatinization of sago starch with the addition of xanthan gum was significantly lower than that containing locust bean or carrageenan gums. The starch gelatinization enthalpy (AH) of the dough containing locust bean gums was the highest among the hydocolloids. The effects of the hydrocolloids on hardness of gel and viscoelastic properties of 'keropok lekor' dough were significantly (P<0.05) dependent on the water binding ability of the gel. The maximum value of loss (G") and storage (G') moduli of mixtures of locust bean-starch and carrageenan-starch increased with the concentration of the gum. However, these moduli decreased in the xanthan gum-starch mixture. The G' of the 'keropok lekor' dough containing 1% and 2% of locust bean and carrageenan gum were higher than that of control and xanthan gum incorporated in the temperature range of fish protein denaturation (from 30 to 76°C). In doughs with 3% incorporation of hydrocolloids, the G' of the dough incorporated with xanthan gum was found to be the highest. However the peak modulus (G') at gelatinization temperature (862°C) of 3% xanthan gum was much lower than that of others. Thus, the textural properties of the 'keropok lekor' incorporated with 3% xantan gum were the lowest among the samples. Examination of the microstructure by light (LM), scanning electron (SEM) and transmission electron (TEM) microscopy indicated that there were interactions between starch, fish protein, and hydrocolloids. The results from SEM studies showed that the sizes and number of cavities were reduced in 'keropok lekor' incorporated with locust bean and carrageenan gum. Thus, carrageenan and locust bean gums increased the textural properties such as hardness, cohesiveness #g@uSIAKAAN SUL'1;m t,#mm#n awrru WWA, and springiness of 'keropok lekor'. In contrast, xanthan gum disrupted the protein networking in the 'keropok lekor' gel, and caused the formation of larger size cavities as observed in SEM, and reduced the size of swollen starch granule in the gel matrix as observed in light micrograph. As a result, xanthan gum significantly decreased the hardness, cohesiveness and springiness of 'keropok lekor'. Among the 3 hydrocolloids evaluated in the present study, locust bean gum was the most effective in increasing the water-binding ability and viscoelastic properties, and it decreased the sizes and numbers of the cavities in the gel that influenced the textural characteristics of the final product. Xanthan gum interfered with the gelation - - process and significantly decreased the viscoelastic properties of the product.